2019
DOI: 10.1101/733832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Density-dependent costs and benefits of male mating success in a wild insect

Abstract: Social environments are important determinant of fitness, particularly when same-sex local densities shape both mating success and survival costs.We studied how mating success varied across a range of naturally occurring local male densities in wild field cricket males, Gryllus campestris, monitored by using fully automated RFID-surveillance system. We predicted that mating success as a function of local density follow a concave pattern predicted by the Allee-effect theory. As increasing density should reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…An individual’s social position in the group can impact its mating behavior in several ways. For instance, connections to conspecifics are fundamentally linked to mate availability, to the degree of intraspecific competition, and to the potential for sexual harassment (e.g., Jirotkul 1999 ; Le Galliard et al 2005 ; Maldonado-Chaparro et al 2018 ; Grant and Grant 2019 ; Niemelä et al 2019 ). Social factors operating at the individual level can generate population-level patterns in terms of which individuals are most likely to breed and with whom they reproduce.…”
Section: Introductionmentioning
confidence: 99%
“…An individual’s social position in the group can impact its mating behavior in several ways. For instance, connections to conspecifics are fundamentally linked to mate availability, to the degree of intraspecific competition, and to the potential for sexual harassment (e.g., Jirotkul 1999 ; Le Galliard et al 2005 ; Maldonado-Chaparro et al 2018 ; Grant and Grant 2019 ; Niemelä et al 2019 ). Social factors operating at the individual level can generate population-level patterns in terms of which individuals are most likely to breed and with whom they reproduce.…”
Section: Introductionmentioning
confidence: 99%
“…Boiteau et al [18], for example, reported high mortality of D. virgifera virgifera due to cyanoacrylate adhesive application. The opposite effect was observed by Niemelä et al [65], who described that RFID tag attachment with cyanoacrylate adhesive did not affect survival of Gryllus campestris Linnaeus, 1758 during 20 days of field observation. In the current study, we did not observe any mortality of G. locorojo following adhesive application.…”
Section: Plos Onementioning
confidence: 77%
“…If the population is large, a minor increase in an individual's signal is expected to have negligible effects on the individual's reproductive gain. If the population is small, a minor increase in an individual's signal may carry with it larger reproductive advantages, as it is easier for signal receivers to target and reward the signaler when there are fewer signalers to navigate between [20,21]. The ability of a receiver to discern between individual signalers, known as phonotactic selectivity, increases the potential reproductive gain given an increase in signal [22,23].…”
Section: Introductionmentioning
confidence: 99%